2021
DOI: 10.3389/fimmu.2021.661990
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of Circulating Immune Cells Is Dysregulated in People Living With HIV on Long Term Antiretroviral Treatment and Relates With Markers of the HIV-1 Reservoir, Cytomegalovirus, and Microbial Translocation

Abstract: Long-term changes in the immune system of successfully treated people living with HIV (PLHIV) remain incompletely understood. In this study, we assessed 108 white blood cell (WBC) populations in a cohort of 211 PLHIV on stable antiretroviral therapy and in 56 HIV-uninfected controls using flow cytometry. We show that marked differences exist in T cell maturation and differentiation between PLHIV and HIV-uninfected controls: PLHIV had reduced percentages of CD4+ T cells and naïve T cells and increased percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 76 publications
2
27
0
Order By: Relevance
“…In fact, including the patients' age did not improve the RF model performance. Age has been evaluated extensively in the past also using the same flow cytometry panels used in the current study [16,17]. Although aging influences the immune cell composition (e.g., young vs old), within the age-interval (mean age 44-56) of our study cohort, as expected and as analyzed, the outcome of the RF model was hardly influenced.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In fact, including the patients' age did not improve the RF model performance. Age has been evaluated extensively in the past also using the same flow cytometry panels used in the current study [16,17]. Although aging influences the immune cell composition (e.g., young vs old), within the age-interval (mean age 44-56) of our study cohort, as expected and as analyzed, the outcome of the RF model was hardly influenced.…”
Section: Discussionmentioning
confidence: 58%
“…All antibodies were titrated and tested before use. Percentages of immune cell subsets were manually analyzed using Kaluza software version 2.1 (Beckman-Coulter, Brea, CA, USA) as described previously [16,17,19].…”
Section: Methodsmentioning
confidence: 99%
“…IL-1β and IL-6 and TNF) in PLHIV. 1 By comparing the cytokine production data of our HIV cohort to 173 samples from the 500FG cohort (different samples from our previous studies 1,36 ), we identified 24 cytokine abundances that were significantly different (Fig. 3a, Supplementary Table 10).…”
Section: Resultsmentioning
confidence: 91%
“…Despite long-term cART, the immune responses of PLHIV are known to be different than those of healthy controls 36 . In a previous study from our group 1 , PBMCs of PLHIV and healthy controls were stimulated ex vivo with 12 different microbial stimuli and the cytokine production capacity assessed, including monocyte-derived (IL-1β, IL-6 and TNF), lymphocyte-derived proinflammatory cytokines (IL-17, IL-22 and IFN-γ) and anti-inflammatory cytokines (IL-10 and IL-1 receptor antagonist, IL-1Ra) (Supplementary Table 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation